The effect of energy price on economic growth and the environment in the European union - Khan, Ali Akbar (Nazarbayev University School of Sciences and Humanities, 2026)
This thesis examines the dynamic relationship between energy prices, economic growth, and environmental quality across 27 European Union member states from 2001 to 2023 using a Panel Autoregressive Distributed Lag (ARDL) model. Long run elasticities indicate that a sustained 10 percentage points increase in energy prices reduces GDP growth by approximately 0.45 percentage points, equivalent to an estimated €78 billion annually at European Union output of €17.3 trillion for the year 2023 (Eurostat, n.d.), while decreasing greenhouse gas emissions growth by roughly 1.3 percentage points. Consequently, achieving a 1 percentage points reduction in emissions growth requires an estimated 7.7 percentage points sustained energy price increase, which entails an annual GDP cost of approximately €59 billion. These findings confirm that energy pricing works as an environmental policy tool, but it comes with real economic costs. The results therefore highlight an inherent policy trade-off between climate benefits and economic output that must be carefully navigated in the implementation of the European Green Deal (European Parliament, n.d.).
Keywords: ENERGY PRICES; ECONOMIC GROWTH; ENVIRONMENT; PQDT_Master